PSA PLATFORM FOR POSTGRADUATE STUDENTS TO EXPAND THEIR HORIZONS - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 31 August 2016 – The Universiti Sains Malaysia (USM) Postgraduate Students Association (PSA) is dedicated to fostering a sense of community and belonging among the postgraduate students at the university towards collective learning, enhancing mobility among them and coming together to organise local and international events.